UJI DAYA HAMBAT EKSTRAK ETANOL DAUN AFRIKA (Vernonia amyygdalina Del.) TERHADAP PERTUMBUHAN propioniumbacterium acnes dan Staphylococcus epidermis - Masyudi Zulkifli (Akademi Farmasi Yamasi Makassar, 2022)
This study aimed to determine the effects and the concentration of ethanol extract of leaves Africa (Vernonia amygdalina Del.) Against Propionibacterium acnes and Staphylococcus epidermidis The design study is a experimental lab that conducted at the Laboratory of Microbiology Department of Pharmacy, Ministry of Health polytechnic Makassar. Africa leaves extracted by maceration using 70% ethanol. African Leaf Extract is made with a concentration of 5%, 10%, and 15% and the Na-CMC solution 1% as a negative control. Testing is done by disc diffusion method using paper disks on medium Nutrient Agar (NA) with an incubation period of 1 x 24 hours at 37 ° C. The results showed that the average value at a concentration of 5% was 8.67 mm, 10% is 10.33 mm and 12.33 mm 15% is for Propionibacterium acnes and average value at a concentration of 5% was 9.33 mm , 10% is 10.33 mm and 15% is 12.33 mm for Staphylococcus epidermidis.Ekstrak African Leaf tested has bacteriostatic effects against bacteria test. Extract as much as 15% resulted in the greatest inhibition against Propionibacterium acnes is 12.33 mm and 12.33 mm, namely Staphylococcus epidermidis.